Medical tourism: how lobby servicescape may influence customers’ image and pleasure - Loureiro, S. M. C.; Ferreira, E. S. (Revista Turismo e Desenvolvimento/Journal of Tourism and Development, 2014)
Medical tourism has become of increasing interest for both researchers and managers in 21st century. However, how lobby servicescape influences customer’s image and pleasure is not well understood. To contribute to address this gap, this study aims to explore the effect of three factors of servicescape on customers’ image and pleasure. So, a sample of 332 fully completely questionnaires were employed to test the proposed model. Findings reveal servicescape as an effective antecedent of customer’s image and pleasure. Finally, the article also attempts to provide managerial implications and suggests further research.